2016
DOI: 10.1007/s11357-016-9920-3
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory insult during pregnancy accelerates age-related behavioral and neurobiochemical changes in CD-1 mice

Abstract: Data shows that inflammation during pregnancy significantly exerts a long-term influence on offspring, such as increasing the risk of adult cognition decline in animals. However, it is unclear whether gestational inflammation affects the neurobehavioral and neurobiochemical outcomes in the motherself during aging. In this study, pregnant CD-1 mice intraperitoneally received lipopolysaccharide (LPS) in two doses (25 and 50 g/kg, respectively) or normal saline daily during gestational days 15-17. At the age of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 81 publications
7
40
1
Order By: Relevance
“…Bacterial infections during pregnancy result in a systemic inflammatory reaction in mothers and can affect cognition in their offspring. Our recent findings suggested that age significantly affected spatial learning and memory from middle age to old age in CD‐1 mice, and maternal exposure to LPS in CD‐1 mice could trigger and exacerbate the age‐related spatial memory impairment in their offspring from middle age onwards in a linear manner (Li, Cao, et al, ; Li, Wang, et al, ). In the current study, we used the same system to mimic maternal systemic inflammation during pregnancy and examined its long‐term effect on recognition and spatial learning and memory in their offspring.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bacterial infections during pregnancy result in a systemic inflammatory reaction in mothers and can affect cognition in their offspring. Our recent findings suggested that age significantly affected spatial learning and memory from middle age to old age in CD‐1 mice, and maternal exposure to LPS in CD‐1 mice could trigger and exacerbate the age‐related spatial memory impairment in their offspring from middle age onwards in a linear manner (Li, Cao, et al, ; Li, Wang, et al, ). In the current study, we used the same system to mimic maternal systemic inflammation during pregnancy and examined its long‐term effect on recognition and spatial learning and memory in their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioral experiments including nesting, open field, beam walking, elevated plus maze, OLR, and RAWM were conducted according to our previous studies (Chen et al, ; Li, Cao, et al, ; Li, Wang, et al, ; Tong et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations